Efficacy and safety of 12 immunosuppressive agents for idiopathic membranous nephropathy in adults: A pairwise and network meta-analysis - Liu, Jiarong; Li, Xiang; Huang, Tianlun; Xu, Gaosi (Frontiers in Pharmacology, 2022)
Background: Immunosuppressants have been applied in the remedy of idiopathic membranous nephropathy (IMN) extensively. Nevertheless, the efficacy and safety of immunosuppressants do not have final conclusion. Thus, a pairwise and network meta-analysis (NMA) was carried out to seek the most recommended therapeutic schedule for patients with IMN. Methods: Randomized controlled trials (RCTs) including cyclophosphamide (CTX), mycophenolate mofetil (MMF), tacrolimus-combined mycophenolate mofetil (TAC + MMF), cyclosporine (CsA), tacrolimus (TAC), leflunomide (LEF), chlorambucil (CH), azathioprine (AZA), adrenocorticotropic hormone (ACTH), non-immunosuppressive therapies (CON), steroids (STE), mizoribine (MZB), and rituximab (RIT) for patients with IMN were checked. Risk ratios (RRs) and standard mean difference (SMD) were reckoned to assess dichotomous variable quantities and continuous variable quantities, respectively. Total remission (TR) and 24-h urine total protein (24-h UTP) were compared using pairwise and NMA. Then interventions were ranked on the basis of the surface under the cumulative ranking curve (SUCRA). Results: Our study finally included 51 RCTs and 12 different immunosuppressants. Compared with the CON group, most regimens demonstrated better therapeutic effect in TR, with RR of 2.1 (95% CI) (1.5–2.9) for TAC, 1.9 (1.3–2.8) for RIT, 2.5 (1.2–5.2) for TAC + MMF, 1.9 (1.4–2.7) for CH, 1.8 (1.4–2.4) for CTX, 2.2 (1.0–4.7) for ACTH, 1.6 (1.2–2.1) for CsA, 1.6 (1.0–2.5) for LEF, and 1.6 (1.1–2.2) for MMF. In terms of 24-h UTP, TAC (SMD, −2.3 (95% CI −3.5 to −1.1)), CTX (SMD, −1.7 (95% CI −2.8 to −0.59)), RIT (SMD, −1.8 (95% CI −3.5 to −0.11)), CH (SMD, −2.4 (95% CI −4.3 to −0.49)), AZA (SMD, −−4.2 (95% CI −7.7 to −0.68)), and CsA (SMD, −1.7 (95% CI −3 to −0.49)) were significantly superior than the CON group. As for adverse effects (AEs), infections, nausea, emesia, myelosuppression, and glucose intolerance were the collective adverse events for most immunosuppressants. Conclusion: This study indicates that TAC + MMF performed the best in terms of TR, and TAC shows the best effectiveness on 24-h UTP compared with other regimens. On the contrary, there seems to be little advantage on STE alone, LEF, AZA, and MZB in treating patients with IMN compared with CON. Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021287013]